Cardiometabolic health, prescribed antipsychotics and health-related quality of life in people with schizophrenia-spectrum disorders: a cross-sectional study. Issue 1 (December 2016) - Bressington, Daniel; Mui, Jolene; Tse, Mei; Gray, Richard; Cheung, Eric; Chien, Wai
Abstract Background People with schizophrenia–spectrum disorders (SSD) often have high levels of obesity and poor cardiometabolic health. Certain types of antipsychotics have been shown to contribute towards weight gain and there is some equivocal evidence that obesity is related to poor health-related quality of life (HRQoL) in people with SSD. It is also still uncertain if antipsychotic polypharmacy/higher doses of antipsychotics are linked with HRQoL and/or increased risk of obesity/Cardiovascular Disease (CVD). Therefore, this study aimed to examine potential relationships between prescribed antipsychotic medication regimens, cardiometabolic health risks and HRQoL in community-based Chinese people with SSD. Method This cross-sectional study reports the results of baseline measurements of a random sample of patients in an ongoing controlled trial of physical health intervention for people with severe mental illness. Data from these randomly-selected participants (n = 82) were analysed to calculate 10-year CVD relative-risk (using QRISK®2 score), estimate the prevalence of metabolic syndrome and contextualize patients' prescribed antipsychotics (types, combinations and Daily Defined Dose equivalent). Patients self-reported their HRQoL (SF12v2) and their obesity condition was assessed by waist-circumference and Body Mass Index (BMI). Results Two-thirds of patients had a BMI ≥23 kg/m2, almost half were centrally obese and 29% met the criteria for metabolic syndrome. The individual relative-risk of CVD ranged from 0.62 to 15, and 13% had a moderate-to-high 10-year CVD risk score. Regression models showed that lower physical HRQoL was predicted by higher BMI and lower mental HRQoL. Higher Defined Daily Dose, clozapine, younger age and male gender were found to explain 40% of the variance in CVD relative risk. Conclusion The findings indicate that cardiometabolic health risks in people with SSD may be more common than those reported in the general Hong Kong population. The results also provide further support for the need to consider antipsychotic polypharmacy and higher doses of antipsychotics as factors that may contribute towards cardiometabolic risk in Chinese patients with SSD. Clinicians in Hong Kong should consider using routine CVD risk screening, and be aware that younger male patients who are taking clozapine and prescribed higher Defined Daily Dose seem to have the highest relative-risk of CVD. Trial registration Clinicaltrials.govNCT02453217 . Prospectively registered on 19th May 2015.